Inhibiting and Supporting Factors for the Production and Income Dynamics of Candied Cashew Entrepreneurs in Pulau Makian - Mansur, Musair; Syahrain, Ruliyanto; Kalengkongan, Yuliana (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This research aims to identify inhibiting and supporting factors in the development of the walnut snack industry and determine strategies for its advancement on Makian Island. The research method employed is qualitative, utilizing the postpositivism paradigm, a philosophical approach that emphasizes empirical phenomena. The primary data for this research were obtained from 8 informants, and data collection techniques included observation, in-depth interviews, and documentation. The results reveal a significant dependence of Suma Village residents on Walnut Snacks for their livelihoods, with a considerable impact on their economic welfare. The presence of the Walnut Snacks business contributes significantly to improving the prosperity of the Suma Village Community. In addition to the cultural values inherent in the local community, social values are also deeply ingrained in every individual within the Suma Village Community.